The Impact of Telehealth Implementation on Increasing Antenatal Care Visits: A Literature Review - Maria Irene Somi Beluan; Sukihananto (Lentera Perawat, 2024)
Antenatal care is an essential service in reducing maternal mortality. However, several studies have shown that distance, cost, time and quality of service affect the decline in ANC visits. For this reason, technology-based innovation (telehealth) is needed to overcome this. The aim was to evaluate the impact of using telehealth on increasing the number of antenatal care visits.  The method used was PRISMA from electronic databases: Scopus, Clinical Key Nursing, Science Direct and Proquest. The results showed that telehealth can expand the range of services, is effective, efficient and flexible in terms of cost and time, and there is no significant difference in the quality of the examination results. In conclusion, through easy access and more efficient costs offered by telehealth, it has a positive impact on increasing the number of antenatal care visits. This also has implications for the world of nursing, not only expanding maternity services but continuing to adapt to the massive development of technology to welcome the era of Society 5.0